ASSESSMENT OF RIVER WATER QUALITY USING MACRO-INVERTEBRATES AS INDICATORS: A CASE STUDY OF BHALU KHOLA TRIBUTARY, BUDHIGANDAKI RIVER, GORKHA, NEPAL - Rana, Anju; Chhetri, Jeevan (International Journal of Environment, 2015)
Macroinvertebrates are widely considered as indicators of water quality. The present research work was conducted in Bhalu khola, a tributary of Budhigandaki River, Nepal, to identify water quality using macro invertebrates with Nepalese Biotic Score (NEPBIOS), and examine its applicability by comparing with Water Quality Index (WQI).The diversity of macro invertebrates in the studied river was high as depicted by Shannon Wiener Diversity Index. Altogether, 103 macro invertebrates were identified from 11 families and five orders. There were no dominant species, and most of the species were in clumped distribution. According to NEPBIOS index, river water was found to comply with the characteristics of WQ class I-II that means water quality of the river was good. Other indices such as Hilsenhoff and Lincoln quality index (LQI) index also supported this result. Similarly, water quality index (WQI) also showed similarity with NEPBIOS index, indicating water appropriate for drinking purpose. Thus, it is concluded that the macro invertebrates can be used as economic tools for determining water quality of streams and rivers as efficient water quality indicators.International Journal of Environment Volume-4, Issue-3, June-August 2015Page: 55-68